PENGETAHUAN DAN SIKAP MAHASISWA S-1 FARMASI UNIVERSITAS SURABAYA TERHADAP UPAYA PENCEGAHAN - Lidya Dian Pratiwi (Perpustakaan Universitas Surabaya, 2014)
Indonesia is the country with the most TB patients of the 5th in the world after India, China, South Africa, and Nigeria (WHO, 2008). Estimated number of TB patients in Indonesia approximately 5.8% of the total number of TB patients in the world. To be able to tackle TB effectively required knowledge and good attitude about TB. Has done research on the knowledge and attitude of students S-1 Pharmacy University of Surabaya in tuberculosis prevention efforts. The research was carried out using the method of cross sectional at 100 S-1 Pharmacy students who are classified proportionally based on the host. Research instrument used was a questionnaire which is divided into two aspects, namely knowledge about tuberculosis and attitude towards tuberculosis prevention efforts. From this research obtained as much as 44% results S-1 Pharmaceutical student has had a high knowledge and 56% have low knowledge about TB. Not found any meaningful difference on the level of knowledge possessed by the respondent based on the host. On the majority of the respondents attitudes, already showed a positive attitude about TB and prevention efforts include: vulnerable people infected with TB are the family members of patients and people with HIV, the main diagnostic tests to make sure the case is a test of TB sputum SMEAR, and the most effective way to prevent contracting TB is by covering the mouth and nose while coughing or sneezing, as well as conducting immunization BCG.